Analisis Risiko Kecelakaan Kerja Dengan Metode HIRARC - Fajar Muhammad Khudhory; Lina Dianati Fathimahhayati; Theresia Amelia Pawitra (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2022)
CV. Jaya Makmur repairs and sells second-hand heavy equipment spare parts. This workshop has an area of about 400 m2 with limited working space due to large number of materials like machines, tools and finished products spread around. When doing work activities, it was often found that workers did not wear complete Personal Protective Equipment (PPE). This condition led some minor work accidents ovvur almost everyday. Due to many potential hazards in CV. Jaya Makmur, analysis related to occupational health and safety needed to be done in order to control the potential hazards. This research aims to identify potential hazards, assess risks, and control the risks in CV. Jaya Makmur using HIRARC method. Based on the results of observations and interviews with a workshop owner and three workers, there were 18 potential hazards. There were also 12 low level risks and 22 moderate level risks. There was some risk control that can be done like engineering control, which is installation of barriers between the source of danger and workers. There were also some administrative control like changing work procedures, conducting supervision and warning, providing training to workers on the importance of occupational safety and health in the workplace, as well as making and performing periodic maintenance on work equipment. In addition, the workers needed to use personal protective equipment like work clothes, face shield, safety glasses, gloves, safety helmet, mask, safety shoes, and earmuff while working.